Genetically Confirmed Spinal Muscular Atrophy Type 3 With Epilepsy In A Malay Patient, A Case Report - Ba, Zilfalil; Ms, Watihayati; My, Rozainah; R, Sutomo; H, Nishio; M, Matsuo; Hussin, Zabidi (2003)

(untitled)
Spinal Muscular Atrophy (SMA) is an autosomal recessive disease affecting the anterior horn cells of the spinal cord. The diagnosis is usually based on the clinical presentation with or without muscle biopsy and the molecular detection of mutation in the SMNI gene. There have been a few reported cases of SMA with central nervous system involvement, but these were without genetic diagnoses. We report a Malay girl with genetically confirmed SMA complicated by epilepsy. She first presented with motor weakness at the age of 17 months and recurrent seizures a month later. The molecular genetic analysis of her SMN gene showed homozygous deletion of exon 7 and 8 of the SMN1 gene. The seizure responded well to carbamazepine. To the best of our knowledge, this is the first case of genetically comfirmed Malay SMA patient with an association with epilepsy.